Immunogenicity and reactogenicity of a 13-valent-pneumococcal conjugate vaccine administered at 2, 4, and 12 months of age: a double-blind randomized active-controlled trial. - Snape, MD; Klinger, C; Daniels, E; John, T; Layton, H; Rollinson, L; Pestridge, S; Dymond, S; Galiza, E; Tansey, S; Scott, D; Baker, SA; et al. (2010)
BACKGROUND: A 2-, 4-, and 12-month schedule of a novel 13-valent-pneumococcal conjugate vaccine (PCV13), containing serotype 1, 3, 4, 5, 6A, 6B 7F, 9V, 14, 18C, 19A, 19F, and 23F polysaccharides individually conjugated to CRM197 was evaluated in a randomized, double-blind, controlled infant study. METHODS: Two hundred eighty-six healthy infants received PCV13 or the 7-valent-pneumococcal conjugate vaccine (PCV7) at 2, 4, and 12 months of age, alongside a serogroup C meningococcal (MenC) vaccine (2 and 4 months of age), DTaP-IPV-Hib (2, 3, and 4 months), and a Hib-MenC vaccine (12 months). Specific antibody responses were assessed at age 5, 12, and 13 months. RESULTS: At 13 months of age, >97% of PCV13 recipients had pneumococcal serotype-specific serum IgG concentrations ≥0.35 µg/mL for each vaccine serotype except serotype 3 (88.2%), and at least 93% of PCV13 recipients had OPA titers ≥1:8 for each serotype. At 5 months, 110/114 (96.5%) of PCV13 recipients and 100/102 (98.0%) of PCV7 recipients had serum anti-PRP (Hib) IgG concentration ≥0.15 µg/mL (difference, 1.5%; CI, -7.1%–3.7%), while 119/120 (99.2%) and 117/118 (99.2%), respectively, had MenC serum bactericidal assay titers of ≥1:8. All PCV13 recipients and 110/113 (97.3%) of PCV7 recipients had IgG concentrations against fimbrial agglutinogens of ≥2.2 EU/mL; IgG concentrations for the remaining pertussis antigens were ≥5 EU/mL for all participants. Local reactions and systemic events were similar in the PCV13 and PCV7 groups. CONCLUSIONS: A 2-, 4-, and 12-month course of PCV13 was immunogenic for all 13 vaccine serotypes and was well tolerated.